PENGARUH IMPLEMENTASI PROGRAM DIKLAT STRUKTURAL PNS TERHADAP TINGKAT KOMPETENSI KEPEMIMPINAN APARATUR DI SEKRETARIAT DAERAH KABUPATEN KEPULAUAN SITARO - Makasihi, Erlin A. (ACTA DIURNA KOMUNIKASI, 2013)
The Influence of Structural in Implementation Program for Education and Training of Civil Officials Towards the Competence Degree of Apparatus Leadership in Regional Secretariate of Isles of Sitaro. Based on the indicators of the research, it is clear that the structural implementation program for education and training in regency of Sitaro and the leadership competence of apparatus is not yet maximal. However, based or linier regression analysis and product moment correlation it is shown that the structural implementation program for education and training of civil officials influences positively and significantly to the leadership competence of apparatus in regional secretariate of isles of Sitaro Regency. That is why, the structural implementation program for education and training is a determined factor to the competence degree of apparatus leadership. Keyword : implementation program, leadership apparatus and competence degree.